Effect of benson's relaxation technique on anxiety in family caregivers of patients with cancer: A randomized controlled trial - Bahareh Ebrahimi; Mohsen Adib-Hajbaghery (Kashan University of Medical Sciences, 2022)
Background: Family caregivers of patients with cancer experience high levels of anxiety and mental health problems. Relaxation methods have seldom been used in these caregivers. Objectives: This study tested the effect of Benson's relaxation method (BRM) on state anxiety in family caregivers of patients with cancer. Methods: A randomized controlled trial was conducted on 50 primary family caregivers of patients with cancer. Family caregivers were randomly assigned to a control group and an experimental group, each group consisted of 25 people. In the experimental group, the subjects were trained to practice the BRM at home, once a day for 6 weeks. Family caregivers' anxiety was measured at the start of the study and at the end of the 6th and 10th weeks by using Spielberger's State Anxiety Inventory (i.e., form y-1). The data were analyzed using descriptive and inferential statistics such as the Fisher's exact, independent samples t, and Mann-Whitney U tests as well as the repeated-measures analyses of variance. Results: No significant difference was found between the mean baseline state anxiety of the control and experimental groups (P = 0.329). However, during the study, the mean anxiety was decreased in the experimental group, whereas it did not significantly change in the control group. The repeated-measures analysis showed that BRM could significantly reduce the mean state anxiety (P <0.001) over time. Conclusion: Regular use of BRM for 6 weeks could decrease the mean scores of state anxiety in family caregivers of patients with cancer. Nurses and other healthcare providers are suggested to teach BRM to the family caregivers of cancer patients and advise them to use this method regularly for the reduction of their own anxiety.